The Effect of the Team-Games-Tournament Method on Improving the Learning Ability of Student with Hearing Impairment in Multiplication Concepts - Rusyani, Endang; Saepulloh, Anwar; Maryanti, Rina; Ragadhita, Risti; Al Husaeni, Dwi Fitria (Indonesian Journal of Multidiciplinary Research, 2021)
This study aimed to evaluate and analyse the results of mathematics learning about the concept of multiplication in students with hearing impairment. In this study, the team-games-tournament (TGT) method was used to teach the concept of multiplication to seven students with hearing impairment in an elementary school at the Special School in Cimahi through four stages of learning, namely: 1) pretest presentation, 2) learning presentation with the TGT method, and 3) posttest presentation. The results of the study showed that there was a significant increase in the ability to learn multiplication concepts using the TGT method. Therefore, the TGT method could be a suitable choice of learning method used in learning the multiplication concept for students with hearing impairment because, through the TGT method, students collaborate and teach each other in-game activities, that make the students understand the concept of multiplication easier, thus improve students' ability to learn the concept of multiplication. This research is important because it provides information about the use of new and unique media or learning methods that can be used to improve students' abilities, especially students with hearing impairments in the mathematics learning process.